In a valley of violence [videorecording (DVD)] - West, Ti, 1980-; Hawke, Ethan, 1970-; Travolta, John, 1954-; Farmiga, Taissa, 1994- (Universal Pictures Home Entertainment, 2016)
Paul is a lone drifter who wanders into the forgotten town of Denton, Texas, dubbed by the locals as the valley of violence. There, he picks a fight with the wrong man, Gilly, the troublemaking son of the town's unforgiving marshal. As tensions arise between Paul and Gilly, an inevitable act of violence starts a disastrous chain reaction that quickly drags the whole town into the bloody crosshairs of revenge. Can the world weary Marshal stop the violent hysteria?